Comparison of 3 cell-free matrix scaffolds used to treat osteochondral lesions in a rabbit model - Demir, Ahder İrem; Pulatkan, Anıl; Uçan, Vahdet; Yılmaz, Bengi; Tahmasebifar, Aydın; Tok, Olgu Enis; Tuncay, İbrahim; Elmalı, Nurzat; Öztürk, Burak Yağmur; Uzer, Gökçer (SAGE Publications Inc., 2022)
Background: Various cell-free scaffolds are already in use for the treatment of osteochondral defects (OCDs); however, a gold standard material has not yet been defined. Purpose: This study compared the macroscopic, histological, and scanning electron microscopy (SEM) characteristics of Chondro-Gide (CG), MaioRegen (MA), and poly-d,l-lactide-co-caprolactone (PLCL) cell-free scaffolds enhanced with small-diameter microfractures (SDMs) for OCDs in a rabbit model. Study Design: Controlled laboratory study. Methods: In total, 54 knees from 27 rabbits were used in this study. Three rabbits were sacrificed at the beginning of the study to form an intact cartilage control group (group IC). An OCD model was created at the center of the trochlea, and SDMs were generated in 24 rabbits. Rabbits with OCDs were divided into 4 groups (n = 12 knees per group) according to the cell-free scaffold applied: CG (group CG), MA (group MA), PLCL (group PLCL), and a control group (group SDM). Half of the rabbits were sacrificed at 1 month after treatment, while the other half were sacrificed at 3 months after treatment. Healed cartilage was evaluated macroscopically (using International Cartilage Regeneration & Joint Preservation Society [ICRS] classification criteria) and histopathologically (using modified O’Driscoll scores and collagen staining). Additionally, cell-free scaffold morphologies were compared using SEM analysis. Results: ICRS and modified O’Driscoll classification and staining with collagen type 1 and type 2 demonstrated significant differences among groups at both 1 and 3 months after treatment (P <.05). The histological characteristics of the group IC samples were superior to those of all other groups, except group PLCL, at 3 months after treatment (P <.05). In addition, the histological properties of group PLCL samples were superior to those of group SDM samples at both 1 and 3 months after treatment in terms of the modified O’Driscoll scores and type 1 collagen staining (P <.05). Concerning type 2 collagen staining intensity, the groups were ranked from highest to lowest at 3 months after treatment as follows: group PLCL (30.3 ± 2.6) > group MA (26.6 ± 1.2) > group CG (23.3 ± 2.3) > group SDM (18.9 ± 0.9). Conclusion: OCDs treated with enhanced SDM using cell-free PLCL scaffolds had superior histopathological and microenvironmental properties, more hyaline cartilage, and more type 2 collagen compared with those treated using CG or MA scaffolds. Clinical Relevance: OCDs treated with PLCL cell-free scaffolds may have superior histopathological properties and contain more type 2 collagen than do OCDs treated with CG or MA cell-free scaffolds.
Keywords: Acellular; Animal Study; Cartilage; Cell-Free; Osteochondral Defect; Scaffold; Small-Diameter Microfracture